Energizing scholarly activity in a regional medical campus - Bell, Amanda; Khemani, Ekta; Weera, Seddiq; Henderson, Chris; Chambers, Larry W (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Implication StatementMedical education is increasingly delivered at distributed sites away from Academic Health Sciences Centres. The Council of Ontario Faculties of Medicine recommends schools develop resources and metrics to foster regional campus scholarly activity.   Opportunities for distributed program trainees must support learning core skills in research and critical appraisal to comply with medical school accreditation standards and to develop their interests and skills in scholarly work for their future medical careers.  We describe a scholarly activity program that is a template for distributed campuses or regional teaching sites seeking to increase learner and faculty engagement and research productivity.